Ratio of carbon and nitrogen in fertilizer treatment drives distinct rhizosphere microbial community composition and co-occurrence networks - Zhu, Ruifen; Liu, Chang; Xu, Yuan Dong; He, Wei; Liu, Jielin; Chen, Jishan; An, Yajun; Shi, Shangli (Frontiers in Microbiology, 2022)
Fertilization is the main strategy to accelerate vegetation restoration and improve rhizosphere microbial community in northeast of China. However, it is largely unknown that the response of rhizosphere microbial community structures, specific microbial taxa, and co-occurrence patterns to fertilization with cow manure in grassland (only alfalfa). In this study, the variation of bacterial community structures in R_Manure (extracted liquid of fermented cow manure), E_Manure (extracted residue of fermented cow manure), F_Manure (full fermented cow manure), and Control (without of fermented cow manure) collected from the rhizosphere microbial community of alfalfa were analyzed by application of an Illumina HiSeq high-throughput sequencing technique. A total of 62862 microbial operational taxonomic units (OTUs) were detected, and derived from 21 phyla known bacteria. The dominant bacteria in rhizosphere include Proteobacteria (70.20%), Acidobacteria (1.24%) Actinobacteria (2.11%), Bacteroidetes (6.15%), Firmicutes (4.21%) and Chlorofexi (2.13%) accounting for 86% of the dominant phyla in all treatments. At the genus level, the dominant genus include NB1-j, Lysobacter, Alphaproteobacteria, Subgroup_6, Actinomarinales and so on with the average relative abundance of 1.76%, 1.52%, 1.30%, 1.24%, 1.61%, respectively. Bacterial diversities and community structures were significantly differentiated by different treatments of fertilization. The results of community structure composition showed that R_Manure treatment significantly increased the population abundance of Firmicutes, Chlorofexi and Patescibacteria by 34. 32%, 6.85 and 2. 70%. Through the analysis of the molecular ecological network (MENA), the co-occurrence networks had the shorter average path distance and diameter in R_Manure than in others, implying more stable to environment changes. Redundancy analysis (RDA) showed that ratio of carbon and nitrogen (C/N) was the main factor affecting rhizosphere microbial community composition, while driving distinct rhizosphere bacterial community and its co‑occurrence networks. The R_Manure associated with more C/N had a relatively complex microbial co‑occurrence networks with a large number of nodes and edges, while the microbial network of others associated with less C/N had fewer taxa with loose mutual interactions. These results suggested that organic fertilizer with high C/N can regulate the rhizosphere microorganism, while high C/N can determine bacterial community structures, and their relationships with the nodule size of alfalfa.